2013
DOI: 10.1128/jvi.02824-12
|View full text |Cite
|
Sign up to set email alerts
|

Response of Hepatitis C Virus to Long-Term Passage in the Presence of Alpha Interferon: Multiple Mutations and a Common Phenotype

Abstract: H epatitis C virus (HCV) infects an estimated 180 million people worldwide, and about 75% of newly infected patients progress toward a chronic infection, which constitutes a risk for severe liver diseases such as cirrhosis and hepatocarcinoma (1-4). HCV is a hepacivirus in the Flaviviridae family characterized by the error-prone replication and quasispecies dynamics typical of RNA viruses (2,(5)(6)(7). No vaccine is available to prevent HCV infections or disease, and the current standard of care treatment cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
172
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(188 citation statements)
references
References 130 publications
(131 reference statements)
10
172
4
Order By: Relevance
“…1). Supporting this observation, we and others previously showed that IFN-␣ treatment suppressed viral infection in Huh7.5 cells (24,38,40,(45)(46)(47). In addition, in cells from a typical transfection experiment, as shown in Fig.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…1). Supporting this observation, we and others previously showed that IFN-␣ treatment suppressed viral infection in Huh7.5 cells (24,38,40,(45)(46)(47). In addition, in cells from a typical transfection experiment, as shown in Fig.…”
Section: Discussionsupporting
confidence: 60%
“…13). Finally, Perales et al found that control virus populations serially passaged without IFN-␣ acquired multiple putative cell culture adaptive mutations and showed a certain level of IFN-␣ resistance (40). For the escape experiments done in our study (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IFN-α is a soluble cytokine known for its antiviral and immunotherapeutic properties by regulating a diverse set of cytokines (42) and linking innate cell-mediated responses to the adaptive immune response (43). LPS is a natural ligand for the stimulated secretion of IFN-α.…”
Section: Discussionmentioning
confidence: 99%